EIC451 : Intercultural communication / Academy of Language Studies - UiTM, Academy of Language Studies (Universiti Teknologi MARA (UiTM), 2020)
This course is designed to create awareness of the important role culture plays in intercultural communication. The course is also aimed at highlighting the cultural dimensions in and the barriers to communication across cultures.